Enhancement of Electron Collection and Light Trapping of Inclined GaN and AlGaN Nanowire Arrays. Issue 2 (11th January 2021) - Liu, Lei; Lu, Feifei; Tian, Jian; Zhangyang, Xingyue
Abstract : The structural design of excellent absorption and electron collection is the main challenge of the nanowire array (NWA) photocathode. Herein, the light trapping and photoemission performance of GaN and graded compositional AlGaN‐inclined NWA are systematically researched. The finite‐difference time domain method (FDTD) is used to calculate the light absorption under different inclined angles and array spacings. The results show that the NWA with an inclined angle of 0.4°–0.6° has greater light‐trapping capacity, which obtains up to 97% light absorption at a wavelength of 267 nm. The inclined graded compositional AlGaN NWA with a built‐in electric field has better photoemission performance. The external electric field further improves the electron collection capacity of the NWA cathode. The inclined AlGaN NWA cathode with the best parameters θ = 0.6°, L = 180 nm, and E out = 2 V μm −1 obtains a quantum efficiency of 47.57% and collection efficiency of 31.09%. The study of the inclined graded compositional AlGaN NWA cathode assisted by the electric field provides an effective method for further utilization of incident light and emitted electrons. Abstract : Optical absorption and photoemission of the inclined GaN and graded compositional Al x Ga1− x N nanowire array (NWA) photocathode under external electric field are investigated. The inclined Al x Ga1− x N NWA photocathode can obtain light absorption of 97%, quantum efficiency of 47.57%, and collection efficiency of 31.09%.